Evaluation of Logic Model in Improving the Accuracy of Logistic Model in National PAI Assessment - Safiuddin (EduBase : Journal of Basic Education, 2025)
Objective: This study aims to evaluate the implementation of a logic model on the accuracy level of the logistic model with the probability of correct answers in the National Examination of Islamic Education subjects in East Jakarta. Novelty: This study also highlights the integration of a logic model and logistic regression in evaluating the accuracy of assessment results, offering a new perspective for improving the evaluation of Islamic Education learning outcomes. Methods: The research uses a quantitative approach with logistic regression model evaluation to analyze the accuracy of correct answer probabilities given by the exam participants. The sample consists of 300 respondents who are students from various schools in East Jakarta who took the National Examination for Islamic Education. Data were collected from exam results and analyzed using a logistic regression model to identify the factors influencing the accuracy of correct answers. Results: The findings indicate that the logistic model can provide an accurate representation of the probability of correct answers, with factors such as understanding of the material, student readiness, and teaching methods having a significant impact on exam results. Conclusions: Based on the logic model evaluation, it can be concluded that the implementation of this model is effective in improving the accuracy of exam result predictions and provides further insights into factors that need to be considered in enhancing the quality of Islamic Education learning.